A positive electrode material, a preparation method and application thereof

CN122950465APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611015953.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对目前正极材料与固态电解质复合后存在接触特性差,显著增大界面电阻,需要对应设计高压运行体系的缺陷和不足,本发明的目的在于提供一种正极材料,通过特定的形态结构特实现与固态电解质的良好接触,在低压力下即可具备高容量和循环稳定性,满足快充需求

Benefits of technology

本发明提供了一种正极材料通过控制次颗粒尺寸、比表面积、粒度分布和二次颗粒内部的致密化程度使浸润因子A大于等于0.35,有效减少了内部孔隙结构,避免了在固态电解质渗透不到颗粒内部时,因孔隙多而造成的颗粒之间接触不好,电连接断路增加界面电阻,且形状规则,尺寸均匀的正极材料可增加与固态电解质的有效接触面积,有利于固态电解质在材料颗粒之间的“流动”和“浸润”,正极材料与固态电解质具有良好的接触特性,降低了固固界面电阻,在低压力下即可具有高容量和循环稳定性,满足快充需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention provides a cathode material, its preparation method, and its application, relating to the field of solid-state battery technology. The cathode material of this invention comprises secondary particles formed by the agglomeration of primary particles. The wetting factor of the cathode material is A≥0.35, where A=Dv50 / (N×K90×BET), N is the number of closed pores on the cross-section of a single secondary particle, Dv50 is the median particle size of the secondary particle (in μm), and BET is the specific surface area of ​​the secondary particle (in m²). 2 / g; K90 is the particle size distribution coefficient of secondary particles. The wetting factor A of the positive electrode material of this invention is greater than or equal to 0.35, which effectively reduces the influence of the internal pore structure on the interface resistance and increases the effective contact area with the solid electrolyte. The positive electrode material and the solid electrolyte have good contact characteristics, reducing the solid-solid interface resistance. It can achieve high capacity and cycle stability under low pressure and meet the requirements of fast charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and in particular to a cathode material, its preparation method, and its application. Background Technology

[0002] In recent years, the new energy vehicle industry has developed rapidly, and power batteries are upgrading towards higher energy density, higher safety, longer cycle life, and ultra-fast charging. Solid-state batteries, with their high energy density and intrinsic safety advantages, have become the core technology direction for the next generation of power batteries. Cathode materials, as one of the four key materials for power batteries, directly determine the cell's energy density, fast-charging performance, and cycle stability. For on-board supercharging scenarios, they not only require high specific capacity and high voltage output but also need to be compatible with rapid ion transport and stable interface contact, placing stringent requirements on material structure design and interface compatibility. All-solid-state batteries, which replace traditional liquid electrolytes and separators with solid electrolytes, theoretically offer significantly better energy density and safety performance than liquid lithium-ion batteries, and have become a key focus of industry research and industrialization. However, existing all-solid-state batteries generally suffer from the core bottleneck of poor solid-solid interface contact and high interface impedance, hindering lithium-ion transport and resulting in poor fast-charging performance and the inability to achieve fast charging. To improve interface contact, existing technologies typically require applying high external pressure to the battery, forcing the electrodes and electrolyte to fit tightly together. This not only significantly increases the complexity of battery pack structure design, assembly difficulty, and system weight, but also raises the threshold and cost of mass production manufacturing. Even if a single cell has high energy density, the complex pressurization structure and PACK integration design will significantly reduce the system-level energy density, and the overall performance is actually inferior to that of traditional liquid systems.

[0003] In summary, existing all-solid-state battery material systems and interface designs cannot simultaneously achieve low impedance, fast charging capability, and low-voltage operation. There is an urgent need to develop material systems and interface control schemes adapted to low-pressure operating conditions, so that the cells can achieve high capacity and cycle stability under relatively low operating pressure, and meet fast charging requirements. Summary of the Invention

[0004] To address the shortcomings and deficiencies of current cathode materials combined with solid electrolytes, such as poor contact characteristics, significantly increased interfacial resistance, and the need for corresponding high-voltage operating systems, the present invention aims to provide a cathode material that achieves good contact with solid electrolytes through specific morphological and structural characteristics, thereby possessing high capacity and cycle stability under low pressure and meeting fast charging requirements.

[0005] Another objective of this invention is to provide a method for preparing a positive electrode material.

[0006] Another object of the present invention is to provide a positive electrode sheet.

[0007] Another object of the present invention is to provide a battery cell.

[0008] Another object of the present invention is to provide a battery cell module.

[0009] Another object of the present invention is to provide a battery pack.

[0010] Another object of the present invention is to provide an electrical device.

[0011] In a first aspect, the present invention protects a cathode material comprising secondary particles formed by the agglomeration of primary particles, wherein the wetting factor of the cathode material is A≥0.35, where A=Dv50 / (N×K90×BET), where N is the number of closed pores on the cross-section of a single secondary particle; Dv50 is the median particle size of the secondary particle in μm; and BET is the specific surface area of ​​the secondary particle in m². 2 / g; K90 is the particle size distribution coefficient of secondary particles.

[0012] According to the positive electrode material protected by the present invention, preferably, the wetting factor A of the positive electrode material is 0.35-3.70, more preferably 1.0-3.0.

[0013] In the positive electrode material protected by the present invention, preferably, N is 5-25.

[0014] According to the positive electrode material protected by the present invention, preferably, the Dv50 is 4-10 μm, and / or, K90 ≤ 0.65, and / or, BET ≤ 0.7 μm. 2 / g.

[0015] According to the positive electrode material protected by the present invention, preferably, N is 9-15, Dv50 is 5-10 μm, K90 is 0.5-0.6, and BET is 0.45-0.55 μm. 2 / g.

[0016] This invention protects a cathode material comprising secondary particles formed by the agglomeration of multiple primary particles, wherein the secondary particles have a Dv50 of 4-10 μm, and / or a K90 ≤ 0.65, and / or a BET ≤ 0.7 μm. 2 / g.

[0017] According to the cathode material protected by the present invention, preferably, the primary particles are high-nickel ternary materials with the chemical formula Li. a Ni b Co c Mn d M m N n P pO2, where a, b, c, d, m, and n are represented in mol, b+c+d+m+n+p=1, 1<a<1.1, 0<b<1, 0<c<1, 0<d≤0.5, 0<m≤0.1, 0<n≤0.1, 0<p≤0.1, where M and N can be independently selected from one or more of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.

[0018] Secondly, this invention also specifically protects a method for preparing a positive electrode material, comprising the following steps: S1. A salt solution containing Ni, Co, and Mn, a precipitant solution, and a complexing agent solution are added to the reaction system in parallel streams. The reaction is stirred under an inert atmosphere. The reaction products are then washed, dried, and sieved to obtain the hydroxide precursor material. The concentration of the precipitant solution is 1-10 mol / L, the concentration of the complexing agent solution is 2-9 g / L, the total concentration of Ni, Co, and Mn in the salt solution containing Ni, Co, and Mn is 1-10 mol / L, and the pH of the reaction system is 10.5-12.9. S2. The hydroxide precursor material and lithium source are mixed, an additive containing element M is added, sintered, cooled and crushed to obtain an M-doped ternary cathode material. The M element is selected from one or more of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, and V. The molar ratio of hydroxide precursor to M element is 1:0.0001~0.03.

[0019] According to the method for preparing the cathode material protected by the present invention, preferably, the temperature of the stirring reaction in S1 is 50-70°C, the stirring speed is 100-500 rpm, and the reaction time is 24-60 h.

[0020] According to the method for preparing the cathode material protected by the present invention, preferably, the sintering temperature in S2 is 700-850°C and the time is 10-15h.

[0021] Thirdly, the present invention also specifically protects a positive electrode sheet, comprising a current collector and a positive electrode active layer on the surface of the current collector, wherein the positive electrode active layer uses the positive electrode material as the active substance.

[0022] Fourthly, the present invention also specifically protects a battery cell, including the positive electrode plate.

[0023] Fifthly, the present invention also specifically protects a battery cell module, including the positive electrode sheet or the battery cell.

[0024] In a sixth aspect, the present invention also specifically protects a battery pack, including the positive electrode sheet, the battery cell, or the battery cell module.

[0025] In a seventh aspect, the present invention also specifically protects an electrical device, including the positive electrode sheet, the battery cell, the battery cell module, or the battery pack.

[0026] Beneficial effects: This invention provides a cathode material that, by controlling the secondary particle size, specific surface area, particle size distribution, and internal densification of the secondary particles, achieves a wetting factor A greater than or equal to 0.35. This effectively reduces the internal pore structure, preventing poor contact between particles due to excessive pores when the solid electrolyte cannot penetrate the particle interior, thus avoiding electrical connection breaks and increased interfacial resistance. Furthermore, the regularly shaped and uniformly sized cathode material increases the effective contact area with the solid electrolyte, facilitating the "flow" and "wetting" of the solid electrolyte between the material particles. The cathode material exhibits good contact characteristics with the solid electrolyte, reducing the solid-solid interfacial resistance. It can achieve high capacity and cycle stability under low pressure, meeting the requirements of fast charging. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0028] Figure 1 This is a schematic diagram of the cathode material structure, where 101 is the primary particle, 102 is the secondary particle, and 103 is the pore inside the secondary particle. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0030] In a specific embodiment, the present invention provides a positive electrode material comprising secondary particles formed by the agglomeration of primary particles. The wetting factor A of the positive electrode material is ≥0.35, where A = Dv50 / (N×K90×BET), N is the number of closed pores on the cross-section of a single secondary particle; Dv50 is the median particle size of the secondary particle in μm; and BET is the specific surface area of ​​the secondary particle in m². 2 / g; K90 is the particle size distribution coefficient of secondary particles.

[0031] It should be noted that: To address the issues of poor solid-solid interface contact and high interfacial resistance between the cathode material and the solid electrolyte in solid-state batteries, this invention reveals that when a cathode material (taking a high-nickel ternary cathode material as an example) is combined with a solid electrolyte, the irregular surface of the cathode material, even with a high modulus of the solid electrolyte (such as a sulfide electrolyte), hinders electrolyte wetting, affects electrical contact, and increases surface resistance. Furthermore, the internal porosity of the cathode material is a significant problem. Since the solid electrolyte cannot penetrate into the interfacial spaces between particles like a liquid electrolyte, a high number of internal pores in the cathode material prevents effective carriers and channels for electron and ion transport within the particles, significantly increasing interfacial resistance.

[0032] The cathode material provided by this invention achieves controllable and uniform particle size distribution through the controllability of the secondary particle size. The secondary particles possess a dense internal structure, effectively reducing internal porosity. This prevents poor contact between particles due to excessive pores when the electrolyte cannot penetrate the particles, thus avoiding electrical connection breaks and increased surface resistance. Simultaneously, these secondary particles have a small specific surface area, good sphericity, regular shape, and uniform size. This structural feature increases the effective contact area with the solid electrolyte. Furthermore, the standardized and uniform cathode particles facilitate the "flow" and "wetting" of the solid electrolyte between the material particles, ensuring sufficient contact. The cathode material exhibits excellent contact characteristics with the solid electrolyte. When the wetting factor A is ≥0.35, the material demonstrates good contact with the electrolyte, exhibiting good capacity and cycle stability under low pressure, meeting fast-charging requirements.

[0033] This invention, by designing the secondary particle size, specific surface area, particle size distribution, and internal densification of the secondary particles, can obtain a cathode material with high capacity and cycle stability under low operating pressure, thus solving the problem of poor solid-solid interface contact in solid-state batteries.

[0034] In this invention, the degree of densification inside the secondary particles is represented by the number of closed pores N on the cross-section of a single secondary particle. The cross-section of a single secondary particle mentioned in this invention is not specifically limited. It can preferably be a cross-section with an equivalent diameter of Dv50±11μm, or it can preferably be a cross-section at the maximum cross-section of a single secondary particle. Both are more conducive to accurately reflecting the number of closed pores inside a single secondary particle.

[0035] In some specific exemplary embodiments, N of the present invention can be determined by the following method: The secondary particles of the cathode material were cut, and a profile with an equivalent diameter of Dv50±1μm was selected as the secondary particle profile to be tested. The number of closed pores in the SEM field of view of the profile was determined. A closed void region was defined as a pore. N was obtained by calculating the average value of 5 secondary particle profiles.

[0036] In this invention, Dv50 is the particle size that accounts for 50% of the volume in the volumetric particle size distribution, and K90 is the particle size distribution coefficient, K90=(Dv90-Dv10) / Dv50.

[0037] The particle size test method is as follows: Particle size was measured using a Malvern 3000 laser particle size analyzer according to the GB / T24533-2019 test method. After obtaining Dv10, Dv50, and Dv90 data, K90 was calculated. K90 = (Dv90 - Dv10) / Dv50.

[0038] The specific surface area was determined as follows: a Microt Tristar 3020 testing device was used, with a loose volume of approximately 1 / 2 to 2 / 3 of the bulb volume and a mass of approximately 2.0 g. The degassing time was 2 hours at 200°C, and multi-point BET was selected. The test conditions P / P0 were 0.05, 0.1, 0.15, 0.2, 0.25, and 0.30.

[0039] In some specific embodiments, in order to further balance capacity and fast charging performance, the wetting factor A of the positive electrode material mentioned in this invention is 0.35-3.70, for example, it can be a point value of 0.35, 0.58, 0.76, 0.81, 1.23, 2.53, 2.96, 3.67 or any range of values, and is more preferably A is 1.0-3.0.

[0040] In some specific embodiments, N mentioned in this invention is 5-25.

[0041] Controlling the number of pores inside the secondary particles of the cathode material can form a dense internal structure. In the internal region of the secondary particles of the cathode material where the electrolyte has not penetrated, reducing the number of pores can enhance the contact between the primary particles that make up the secondary particles and enhance the electrical connection performance. However, at the same time, ensuring a certain number of pores inside the secondary particles can buffer the volume change during charging and discharging. Furthermore, if the number of pores inside the secondary particles of the cathode material is too small, it will affect the diffusion of lithium ions and affect the fast charging performance. Therefore, N in this invention is preferably controlled between 5 and 25.

[0042] In some specific exemplary embodiments, N mentioned in this invention can be, for example, 5, 9, 15, 19, 20, 24, 25, etc., and more preferably 9-15.

[0043] The lower the specific surface area of ​​the secondary particles in the cathode material, the closer their morphology is to spherical. In some specific embodiments, the BET of the secondary particles mentioned in this invention is ≤0.7m. 2 / g, and the lower the K90 value of the secondary particle size distribution system, the more uniform the standard particle size. In some specific embodiments, the secondary particles mentioned in this invention have a K90 ≤ 0.65, and the secondary particles with good sphericity and narrow particle size distribution are uniform in size, which can increase the effective contact area with the solid electrolyte. At the same time, it is also more conducive to the "flow" and "wetting" of the solid electrolyte between the material particles, and fully contact the material particles. Combined with the Dv50 value of 4-10μm of the secondary particles of this invention, it can further synergistically improve the cycle and energy density of the solid battery, improve fast charging performance, and reduce the operating pressure of the solid battery.

[0044] In some preferred exemplary embodiments, N mentioned in this invention is 9-15, Dv50 is 5-10 μm, K90 is 0.5-0.6, and BET is 0.45-0.55 μm. 2 / g.

[0045] In some embodiments, the cathode material mentioned in this invention includes secondary particles formed by the agglomeration of multiple primary particles, wherein the secondary particles have a Dv50 of 4-10 μm, and / or a K90 ≤ 0.65, and / or a BET ≤ 0.7 μm. 2 / g.

[0046] In some specific embodiments, the primary particles mentioned in this invention can be pure lithium nickelate.

[0047] In some specific exemplary embodiments, the primary particles of the cathode material mentioned in this invention can also be lithium-rich manganese-based cathode active materials with the chemical formula Li. 1+x Mn a Ni b Co c M d O2, where 0 < x < 0.33, 0 < a ≤ 0.8, 0 < b ≤ 0.67, 0 < c ≤ 0.2, 0 < d ≤ 0.1, and M is selected from one or more of Al, Zr, Mg, Nb, Ti, V, W, and Sb.

[0048] In some specific embodiments, the primary particles mentioned in this invention are high-nickel ternary materials with the chemical formula Li. a Ni b Co c Mn d M m N n P pO2, where a, b, c, d, m, and n are represented in mol, b+c+d+m+n+p=1, 1<a<1.1, 0<b<1, 0<c<1, 0<d≤0.5, 0<m≤0.1, 0<n≤0.1, 0<p≤0.1, where M and N can be independently selected from one or more of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.

[0049] In some specific exemplary embodiments, the nickel content of the high-nickel ternary material is preferably ≥80 mol%. The chemical formula of the above-mentioned high-nickel ternary material contains doping elements M and N, which can promote grain growth and grain orientation, causing the grains to grow towards the dominant crystal plane, resulting in a cathode material with a higher degree of densification.

[0050] In some specific exemplary embodiments, the chemical formula of the high-nickel ternary material mentioned in this invention contains 0.02 < m ≤ 0.06, 0.01 < n ≤ 0.05, and 0.03 < p ≤ 0.07.

[0051] In a specific embodiment, the present invention also provides a method for preparing a positive electrode material, comprising the following steps: S1. A salt solution containing Ni, Co, and Mn, a precipitant solution, and a complexing agent solution are added to the reaction system in parallel streams. The reaction is stirred under an inert atmosphere. The reaction products are then washed, dried, and sieved to obtain the hydroxide precursor material. The concentration of the precipitant solution is 1-10 mol / L, the concentration of the complexing agent solution is 2-9 g / L, the total concentration of Ni, Co, and Mn in the salt solution containing Ni, Co, and Mn is 1-10 mol / L, and the pH of the reaction system is 10.5-12.9. S2. The hydroxide precursor material and lithium source are mixed, an additive containing element M is added, sintered, cooled and crushed to obtain an M-doped ternary cathode material. The M element is selected from one or more of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, and V. The molar ratio of hydroxide precursor to M element is 1:0.0001~0.03.

[0052] In some specific embodiments, the additive containing element M mentioned in S2 of the present invention may be selected from one or more of oxides, hydroxides, oxalates, and nitrates of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, and V.

[0053] In some specific embodiments, the precipitant solution mentioned in S2 of the present invention is an inorganic alkaline solution, such as sodium hydroxide, sodium carbonate, potassium hydroxide, potassium carbonate, etc.

[0054] In the cathode material preparation method provided by this invention, the preparation and doping steps of the hydroxide precursor material are key steps in achieving control of the particle size Dv50, K90, and specific surface area of ​​the cathode material. They are also crucial for controlling the internal densification of secondary particles formed from primary particle agglomeration. By controlling the concentrations of Ni, Co, and Mn salt solutions, precipitant solutions, and complexing agent solutions, and by adjusting the pH of the reaction system, the metal ion release rate is regulated, allowing the primary particles to agglomerate in an orderly manner, growing into secondary particles with low specific surface area. This results in a final secondary particle size distribution and internal densification. The reaction is carried out under inert gas protection to prevent oxidation of the high-nickel system and effectively control the specific surface area.

[0055] Subsequent washing effectively removes unreacted impurities, preventing them from affecting subsequent sintering processes. Drying removes free water, preventing moisture from causing particle cracking and localized hydrolysis of lithium salts during high-temperature sintering. Sieving removes components of unsuitable size, ensuring the dimensional uniformity of the final cathode material.

[0056] In some specific embodiments, in order to further control the particle size and distribution uniformity of secondary particles, the temperature of the reaction after the precursor metal salt solution, alkaline solution and complexing agent solution are added in parallel is 50-70℃, the stirring speed is 100-500rpm, and the reaction time is 24-60h in the preparation method of the cathode material mentioned in this invention.

[0057] In some specific embodiments, the Ni, Co, and Mn salt solutions mentioned in this invention are obtained by dissolving Ni, Co, and Mn sulfates according to the molar ratio of the chemical formula of the high-nickel ternary cathode material.

[0058] The precipitant can be an inorganic alkaline solution, such as sodium hydroxide or sodium carbonate, and the complexing agent solution can be, for example, an aqueous ammonia solution.

[0059] In some specific exemplary embodiments, the lithium source mentioned in S2 of the present invention is selected from one or more of lithium carbonate, lithium hydroxide, and lithium nitrate.

[0060] In some specific exemplary embodiments, the molar ratio of hydroxide precursor to lithium source in the mixed doping sintering reaction of precursor and lithium source mentioned in S2 of the present invention is 1:1.01~1.05, and the molar ratio of hydroxide precursor to M metal is 1:0.0001~0.03.

[0061] In some specific exemplary embodiments, in order to further control the growth of primary particles and ensure the density and particle size uniformity of secondary particles, the sintering temperature mentioned in S2 of the present invention is 700-850°C, the time is 10-15h, and the atmosphere is air, oxygen or a mixture of air and oxygen.

[0062] In some specific exemplary embodiments, the sintering temperature mentioned in S2 of the present invention can be, for example, a point value or any range of values ​​such as 700°C, 720°C, 730°C, 740°C, 750°C, 770°C, 790°C, 800°C, 850°C, and the sintering time can be, for example, a point value or any range of values ​​such as 10h, 11h, 12h, 13h, 14h, 15h.

[0063] In some specific embodiments, the method for preparing the cathode material mentioned in this invention further includes the following steps: The M-doped cathode material obtained above is mixed with pure water at a mass ratio of 1.5-2.5:1, stirred and filtered at 250-350 rpm to obtain the water-washed M-doped cathode material. The water washing process removes residual alkali from the previous doping and sintering.

[0064] In some specific embodiments, the method for preparing the cathode material mentioned in this invention further includes the following steps: The water-washed M-doped cathode material is mixed again with N and P additives, sintered a second time, and crushed to obtain N and P-coated cathode material, wherein N and P are one or more of the oxides and hydroxides formed by Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B elements.

[0065] Surface coating of secondary particles can improve cycle life and ionic conductivity.

[0066] In some specific exemplary embodiments, the molar ratio of the cathode material to N metal is 1:0.001~0.01, and the molar ratio of the cathode material to P metal is 1:0.001~0.01.

[0067] In some specific exemplary embodiments, the secondary sintering temperature mentioned in this invention is 200-600°C, the time is 6-12 hours, and the atmosphere is air, oxygen, or a mixture of air and oxygen.

[0068] In some specific embodiments, the present invention also provides a specific method for preparing a high-nickel ternary cathode material, comprising the following steps: S1: Dissolve the sulfates of Ni, Co, and Mn in molar ratio to obtain a precursor metal salt solution with a concentration of 1-10 mol / L; prepare a precipitant solution with sodium hydroxide or sodium carbonate at a concentration of 1-10 mol / L; prepare a complexing agent solution with ammonia at a concentration of 2-9 g / L. The salt solution, precipitant solution, and complexing agent solution are added to the reactor in parallel flow for reaction. An inert atmosphere is used for protection, and the pH is controlled at 10.5-12.9, the reaction temperature is 50-70℃, the concentration of ammonia is controlled at 2-9 g / L, the stirring speed is 100-500 rpm, and the reaction time is 24-60 h to obtain a hydroxide precursor slurry. After solid-liquid separation, washing, drying, and sieving of the hydroxide precursor slurry in S2, spherical hydroxide precursor material Ni was obtained. b Co c Mn d (OH)2; S2: Mix spherical hydroxide precursor material and lithium source, add additive containing element M, sinter once in atmosphere furnace, cool and crush to obtain M-doped ternary cathode primary material, M element is selected from any one of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, V; The lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium nitrate. The molar ratio of the spherical hydroxide precursor to the lithium source is 1:1.01~1.05, and the molar ratio of the spherical hydroxide precursor to element M is 1:0.0001~0.03. The sintering temperature is 700-950℃, the time is 6-15h, and the atmosphere is air, oxygen or a mixture of air and oxygen. S3: Mix the ternary cathode primary material in S2 with pure water at a mass ratio of 2:1, stir at 300 rpm for 3 min, filter, and dry the filter cake in a vacuum oven at 150 ℃ for 6 h to obtain the washed material. S4: The material washed by S3 is mixed with additives containing N and P, sintered twice in an atmosphere furnace, and then cooled and crushed to obtain a ternary cathode product coated with N and P elements.

[0069] Among them, the M element in S2 has the effect of promoting grain formation. The additive containing the M element is selected from one or more of the oxides, hydroxides, oxalates, and nitrates of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, and V.

[0070] The N and P additives in S4 are selected from one or more of the oxides and hydroxides formed by Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B elements; the molar ratio of the washed material to N and P elements is 1:0.001~0.01:0.001~0.01. The secondary sintering temperature is 200-600℃, the sintering time is 6-12h, and the atmosphere is air, oxygen, or a mixture of air and oxygen.

[0071] In a specific embodiment, the present invention also provides a positive electrode sheet, comprising a current collector and a positive electrode active layer on the surface of the current collector, wherein the positive electrode active layer uses the positive electrode material as the active substance.

[0072] In some specific exemplary embodiments, the positive electrode active layer mentioned in this invention is obtained by coating and drying a positive electrode slurry obtained by mixing positive electrode active material, sulfide electrolyte, conductive agent and binder, wherein the mass ratio of positive electrode active material, sulfide electrolyte, conductive agent and binder is (70-100):(10-26.5):(0.8-1.5):(0.5-2).

[0073] The sulfide electrolyte is selected from Li10GeP2S. 12 It is at least one of the following: Thio-LISICON, Li2S-P2S5, and sulfide-germanium ore.

[0074] The conductive agent and binder can be selected from any of the commonly used conductive agents and binders in this field. For example, the conductive agent can be selected from single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), acetylene black, SuperP, VGCF (nano-carbon fiber), etc., and the binder can be selected from SBS (styrene-butadiene-styrene block copolymer), HNBR (hydrogenated nitrile rubber), PTFE (polytetrafluoroethylene), butyl rubber, etc.

[0075] In a specific embodiment, the present invention also provides a battery cell, including the positive electrode plate.

[0076] In a specific embodiment, the present invention also provides a battery cell module, including the negative electrode sheet or the battery cell.

[0077] In a specific embodiment, the present invention also provides a battery pack, including the negative electrode sheet, the battery cell, or the battery cell module.

[0078] Solid-state battery products (including cell modules and battery packs) prepared from the cathode material provided by this invention can all operate at low pressure. The operating pressure can be reduced from the existing 300MPa to below 100MPa, preferably to 30-50MPa.

[0079] In a specific embodiment, the present invention also provides an electrical device, including the negative electrode sheet, the battery cell, the battery cell module, or the battery pack.

[0080] In some specific exemplary embodiments, the electrical devices mentioned in this invention include, in particular, vehicles, robots, and embodied devices.

[0081] Example 1 A cathode material (Li 1.03 Ni 0.92 Co0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2), including secondary particles formed by the aggregation of primary particles (such as... Figure 1 As shown in Table 1), the wetting factor of the cathode material is A=Dv50 / (N×K90×BET), where N is the number of closed pores on the cross-section of a single secondary particle with an equivalent diameter of Dv50±1μm, Dv50 is the median particle size of the secondary particle, BET is the specific surface area of ​​the secondary particle, and K90 is the particle size distribution coefficient of the secondary particle.

[0082] Examples 2-8 A cathode material (Li 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2), including secondary particles formed by the agglomeration of primary particles, the wetting factor of the positive electrode material A=Dv50 / (N×K90×BET), where N is the number of closed pores on the cross-section of a single secondary particle with an equivalent diameter of Dv50±1μm, BET is the specific surface area of ​​the secondary particles, and K90 is the particle size distribution coefficient of the secondary particles. The specific differences from Example 1 are shown in Table 1.

[0083] Example 9 A cathode material Li 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 The method for preparing O2 includes the following steps: S1: Dissolve the sulfates of Ni, Co, and Mn in a molar ratio of 92:5:3 to obtain a precursor metal salt solution with a concentration of 2 mol / L. Prepare a 7 mol / L alkaline solution with sodium hydroxide and a complexing agent solution with a concentration of 5 g / L with ammonia. The precursor metal salt solution, alkaline solution, and complexing agent solution were added to the reactor in parallel to carry out the reaction. An inert atmosphere was used for protection. The reaction pH was controlled at 11.1, the reaction temperature at 65℃, the stirring speed at 300 rpm, and the reaction time at 36 h. After the particle size reached 5 μm, the hydroxide precursor slurry was obtained. After solid-liquid separation, washing, drying, and sieving, spherical hydroxide precursor material Ni was obtained from the hydroxide precursor slurry. 0.92 Co 0.05 M 0.03 (OH)2; S2: Spherical hydroxide precursor material and lithium hydroxide were mixed at a molar ratio of 1:1.03, and then 1% mol of aluminum oxalate was added. The mixture was sintered at 750℃ for 12 hours under a pure oxygen atmosphere. After cooling, it was crushed and sieved to obtain polycrystalline primary material Li. 1.03 Ni 0.92 Co 0.05 Mn 0.02 Al 0.01 O2; S3: Mix the polycrystalline primary material and pure water at a mass ratio of 2:1, stir at 300 rpm for 3 min, filter, and dry the filter cake in a vacuum oven at 150 ℃ for 6 h to obtain the washed material. S4: The washed material was mixed with 0.1% mol boric acid and 0.1% mol niobium pentoxide (B and Nb elements were quantified in molar ratio), sintered at 300℃ for 6 hours under a pure oxygen atmosphere, and then crushed after cooling to obtain Li. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.00 1Nb 0.001 O2 cathode material.

[0084] Examples 10-16 A cathode material Li 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 The preparation method of O2 is basically the same as that in Example 9, with the differences shown in Table 2.

[0085] Example 17 A cathode material Li 1.25 Mn 0.55 Ni 0.15 Co 0.15 AL 0.05 O2, including secondary particles formed by the agglomeration of primary particles, the wetting factor of the cathode material A = Dv50 / (N×K90×BET), the number of closed pores N on the cross-section of a single secondary particle with an equivalent diameter of Dv50±μm is 10, Dv50 is the median particle size of the secondary particle is 4μm, and BET is the specific surface area of ​​the secondary particle is 0.8m². 2 / g, K90 is the particle size distribution coefficient of secondary particles, which is 0.9.

[0086] This embodiment 17 also specifically provides a method for preparing a cathode material, including the following steps: S1: Dissolve the sulfates of Ni, Co, and Mn in molar ratio to obtain a precursor metal salt solution with a concentration of 2 mol / L, prepare a 7 mol / L alkaline solution with sodium hydroxide, and prepare a complexing agent solution with a concentration of 5 g / L with ammonia. The precursor metal salt solution, alkaline solution, and complexing agent solution were added to the reactor in parallel to carry out the reaction. An inert atmosphere was used for protection, and the pH was controlled at 11, the reaction temperature at 65℃, the stirring speed at 300 rpm, and the reaction time at 36 h to obtain a hydroxide precursor slurry. After solid-liquid separation, washing, drying, and sieving, spherical hydroxide precursor material Ni was obtained from the hydroxide precursor slurry. 0.15 Co 0.15 M 0.55 (OH)2; S2: Spherical hydroxide precursor material and lithium source are mixed, aluminum hydroxide is added, sintered in an atmosphere furnace, cooled and crushed to obtain primary material doped with Al element. The molar ratio of precursor composite hydroxide to lithium source is controlled at 1:1.04, the molar ratio of total precursor metal to Al is 1:0.05, the sintering temperature is 750℃, the sintering time is 12h, and the atmosphere is oxygen. S3: Mix the primary material doped with AL element and pure water at a mass ratio of 2:1, stir at 300 rpm for 3 min and then filter. Dry the filter cake in a vacuum oven at 150 ℃ for 6 h to obtain the washed material. S4: The washed material is mixed with alumina and sintered at 300℃ for 6 hours in a pure oxygen atmosphere. After cooling, it is crushed to obtain the cathode material Li. 1.25 Mn 0.55 Ni 0.15 Co 0.15 AL 0.05 After washing with O2 and water, the total molar ratio of the matrix powder metal to the coated Al metal is 1:0.02.

[0087] Comparative Example 1 A cathode material Li 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2 includes secondary particles formed by the agglomeration of primary particles. The wetting factor A = Dv50 / (N×K90×BET) = 0.17. The number of closed pores N on the cross-section of a single secondary particle with an equivalent diameter of Dv50±1μm is 50. Dv50 is the median particle size of the secondary particles, which is 5μm. BET is the specific surface area of ​​the secondary particles. K90 is the particle size distribution coefficient of the secondary particles. See Table 1 for details.

[0088] It is prepared by the following method: S1: Dissolve the sulfates of Ni, Co, and Mn in a molar ratio of 92:5:3 to obtain a precursor metal salt solution with a concentration of 2 mol / L. Prepare a 7 mol / L alkaline solution with sodium hydroxide and a complexing agent solution with a concentration of 11 g / L with ammonia. The precursor metal salt solution, alkaline solution, and complexing agent solution were added to the reactor in parallel flow for reaction. An inert atmosphere was used for protection, and the reaction pH was controlled at 13.1, the reaction temperature at 65℃, the ammonia concentration at 5g / L, the stirring speed at 300rpm, and the reaction time at 36h. After the particle size reached 5μm, the hydroxide precursor slurry was obtained. After solid-liquid separation, washing, drying, and sieving, spherical hydroxide precursor material Ni was obtained from the hydroxide precursor slurry. 0.92 Co 0.05 M 0.03 (OH)2; S2: Ni, a spherical hydroxide precursor material 0.92 Co 0.05 Mn 0.03 (OH)₂ and lithium hydroxide were mixed at a molar ratio of 1:1.03, and then 1% mol of aluminum oxalate was added. The mixture was sintered at 760℃ for 12 hours under a pure oxygen atmosphere. After cooling, the mixture was crushed and sieved to obtain polycrystalline primary material Li. 1.03 Ni 0.92 Co 0.05 Mn 0.02 Al 0.01 O2; S3: Mix the polycrystalline primary material and pure water at a mass ratio of 2:1, stir at 300 rpm for 3 min, filter, and dry the filter cake in a vacuum oven at 150 ℃ for 6 h to obtain the washed material. S4: The washed material was mixed with 0.1% mol boric acid and 0.1% mol niobium pentoxide (B and Nb elements were quantified in molar ratio), sintered at 300℃ for 6 hours under a pure oxygen atmosphere, and then crushed after cooling to obtain Li. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.00 1Nb 0.001 O2 cathode material.

[0089] Result detection (1) The performance of the cathode materials of the embodiments and comparative examples of the present invention was measured. The specific measurement methods are as follows: Preparation of the positive electrode sheet: The positive active material, sulfide electrolyte, conductive agent and binder prepared in the above examples and comparative examples are added to a container in a mass ratio of 80:20:1:1. After stirring evenly, a positive electrode slurry is obtained. This slurry is coated on aluminum foil and dried to prepare the positive electrode sheet. The sulfide electrolyte is Li6PS5Cl of silver sulfide germanium ore type, the conductive agent is single-walled carbon nanotubes (SWCNT), and the binder is SBS.

[0090] Battery assembly: In the glove box, the positive electrode, solid electrolyte, and indium negative electrode are stacked in sequence into the solid battery mold, and then cured. The curing temperature is adjusted to 60℃ and the curing time is 24h.

[0091] The mold test pressure is 50 MPa (operating pressure). The first discharge specific capacity is tested by charging to 3.7V with a constant current of 0.1C, then charging to 3.7V with a constant voltage, and then discharging to 1.9V with a 0.1C. Cyclic testing: The mold was tested at a pressure of 50 MPa, at a temperature of 25℃, and at a voltage of 1.9-3.7V, the initial discharge capacity C1 was measured after one cycle of charge-discharge at 1C. After 80 cycles, the discharge capacity C2 was obtained, and the capacity retention rate after 80 cycles was calculated as C2 / C1.

[0092] Example 17 is a lithium-rich cathode material. The difference between it and other examples is that halides are used instead of sulfides in the battery assembly, and Li3InCl6 is selected. The upper limit of voltage in the cycle test is 4.2V.

[0093] The specific test results are shown in Table 1.

[0094] Table 1. Performance test results of the cathode materials of Example 1 and the comparative example.

[0095] Group D50 / μm N K90 BET Infiltration factor A First discharge specific capacity mAh / g 80-cycle capacity retention % Example 1 5 15 0.5 0.54 1.23 215 97.5 Example 2 5.5 20 0.55 0.66 0.76 213 96.5 Example 3 5.2 24 0.58 0.64 0.58 212 96.4 Example 4 5.6 19 0.61 0.6 0.81 210 96.8 Example 5 6 9 0.5 0.45 2.96 212 98.5 Example 6 10 15 0.6 0.44 2.53 214 98.2 Example 7 4 25 0.65 0.7 0.35 217 96.2 Example 8 5.5 5 0.6 0.5 3.67 210 99 Example 17 4 10 0.9 0.8 0.56 240 95.3 Comparative Example 1 5 50 0.8 0.75 0.17 200 80.5 As can be seen from the data in Table 1, the wetting factor A of the cathode material provided by this invention is ≥0.35. By controlling the size uniformity and specific surface area of ​​the secondary particles, a cathode material with regular shape and uniform size is obtained, which can increase the effective contact area with the solid electrolyte. At the same time, by controlling the number of pores inside the secondary particles, a dense structure is achieved, avoiding poor contact between particles caused by too many pores when the electrolyte cannot penetrate into the particles, thus preventing electrical connection breakage and increased surface resistance. This achieves good contact between the cathode material and the solid electrolyte, solving the problem of poor solid-solid interface contact in solid batteries. A cathode material with high capacity and cycle stability under low operating pressure can be obtained, meeting the requirements of fast charging.

[0096] In contrast, Comparative Example 1 could not achieve the wetting factor of the cathode material of the present invention, and its initial discharge specific capacity and capacity retention rate after 80 cycles both showed a significant decrease compared to the present invention.

[0097] (2) The structural characteristics of the cathode materials prepared by the methods of the embodiments and comparative examples of the present invention were measured. The specific measurement methods are as follows: The degree of densification within the secondary particles of this invention is represented by the number N of closed pores on a cross-section with an equivalent diameter of Dv50±1μm for a single secondary particle, and can be specifically determined by the following method: The secondary particles of the cathode material were laser-cut, and a cross-section with an equivalent diameter of Dv50±1μm was selected as the cross-section of the secondary particle to be tested. The number of closed pores in the SEM field of view of the cross-section was determined. A closed void region was defined as a pore, and N was obtained by calculating the average value of 5 secondary particle cross-sections.

[0098] Particle size was measured using a Malvern 3000 laser particle size analyzer according to the GB / T24533-2019 test method. After obtaining Dv10, Dv50, and Dv90 data, K90 was calculated. K90 = (Dv90 - Dv10) / Dv50.

[0099] The specific surface area was determined as follows: a Microt Tristar 3020 testing device was used, with a loose volume of approximately 1 / 2 to 2 / 3 of the bulb volume and a mass of approximately 2.0 g. The degassing time was 2 hours at 200°C, and multi-point BET was selected. The test conditions P / P0 were 0.05, 0.1, 0.15, 0.2, 0.25, and 0.30.

[0100] The specific test results are shown in Table 2 below.

[0101] Table 2. Preparation process of cathode materials in the examples and comparative examples Group ammonia concentration pH reaction temperature rotational speed Synthesis time Doping elements Sintering temperature Sintering time D50 / μm N K90 BET Infiltration factor A Example 9 5 11.1 65 300 36 Al 750 12 5 15 0.5 0.54 1.23 Example 10 1 11.5 65 300 36 Al 720 12 5.5 20 0.55 0.66 0.76 Example 11 5 12.9 63 300 36 Al 730 12 5.2 24 0.58 0.64 0.58 Example 12 5 11.3 50 300 36 Al 740 12 5.6 19 0.61 0.6 0.81 Example 13 5 11.5 65 100 36 Al 770 12 6 9 0.5 0.45 2.96 Example 14 5 11.6 65 300 60 Al 770 12 10 15 0.6 0.44 2.53 Example 15 6 10.5 65 300 24 Al 730 12 4 25 0.65 0.7 0.35 Example 16 5 11.3 64 300 36 Al 790 15 5.5 5 0.6 0.5 3.67 Comparative Example 1 11 13.1 65 300 36 Al 760 12 5 50 0.8 0.75 0.17 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that, The cathode material includes secondary particles formed by the aggregation of multiple primary particles, and the wetting factor A is greater than or equal to 0.35, where A = Dv50 / (N×K90×BET). Where N is the number of closed pores on the profile of a single secondary particle; Dv50 is the median particle size of the secondary particle, in μm; and BET is the specific surface area of ​​the secondary particle, in m². 2 / g; K90 is the particle size distribution coefficient of secondary particles.

2. The cathode material according to claim 1, characterized in that, The wetting factor A of the positive electrode material is 0.35-3.70, preferably 1.0-3.

0.

3. The cathode material according to claim 1 or 2, characterized in that, The value of N is 5-25.

4. The cathode material according to claim 3, characterized in that, The Dv50 is 4-10 μm, and / or, K90 ≤ 0.65, and / or, BET ≤ 0.7 m. 2 / g.

5. The cathode material according to any one of claims 1-4, characterized in that, The N is 9-15, Dv50 is 5-10 μm, K90 is 0.5-0.6, and BET is 0.45-0.55 m. 2 / g.

6. A positive electrode material, characterized in that, This includes secondary particles formed by the aggregation of multiple primary particles, wherein the secondary particles have a Dv50 of 4-10 μm, and / or a K90 ≤ 0.65, and / or a BET ≤ 0.7 m. 2 / g.

7. The cathode material according to claim 6, characterized in that, The primary particles are high-nickel ternary materials with the chemical formula Li. a Ni b Co c Mn d M m N n P p O2, where a, b, c, d, m, and n are represented in mol, b+c+d+m+n+p=1, 1<a<1.1, 0<b<1, 0<c<1, 0<d≤0.5, 0<m≤0.1, 0<n≤0.1, 0<p≤0.1, where M and N can be independently selected from one or more of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.

8. A method for preparing a positive electrode material, characterized in that, Includes the following steps: S1. A salt solution containing Ni, Co, and Mn, a precipitant solution, and a complexing agent solution are added to the reaction system in parallel streams. The reaction is stirred under an inert atmosphere. The reaction products are then washed, dried, and sieved to obtain the hydroxide precursor material. The concentration of the precipitant solution is 1-10 mol / L, the concentration of the complexing agent solution is 2-9 g / L, the total concentration of Ni, Co, and Mn in the salt solution containing Ni, Co, and Mn is 1-10 mol / L, and the pH of the reaction system is 10.5-12.

9. S2. The hydroxide precursor material and lithium source are mixed, an additive containing element M is added, sintered, cooled and crushed to obtain an M-doped ternary cathode material. The M element is selected from one or more of Al, Zr, Y, Ti, Sb, W, Sb, Ce, Mg, Mo, and V. The molar ratio of hydroxide precursor to M element is 1:0.0001~0.

03.

9. The method for preparing the cathode material according to claim 8, characterized in that, The stirring reaction described in S1 is carried out at a temperature of 50-70℃, a stirring speed of 100-500 rpm, and a reaction time of 24-60 h. And / or, the sintering temperature described in S2 is 700-850℃, and the time is 10-15h.

10. A positive electrode sheet, comprising a current collector and a positive active layer on the surface of the current collector, characterized in that, The positive electrode active layer is made of the positive electrode material described in any one of claims 1-7 or the positive electrode material prepared by the preparation method described in claim 8 or 9.

11. A battery cell, characterized in that, Includes the positive electrode sheet as described in claim 10.

12. A battery cell module, characterized in that, It includes the positive electrode sheet of claim 10 or the battery cell of claim 11.

13. The cell module according to claim 12, characterized in that, The operating pressure of the battery cell module is less than or equal to 100 MPa, preferably 30-50 MPa.

14. A battery pack, characterized in that, Includes the positive electrode sheet of claim 10, the battery cell of claim 11, or the battery cell module of claim 12 or 13.

15. An electrical appliance, characterized in that, Includes the positive electrode sheet of claim 10, the cell of claim 11, the cell module of claim 12 or 13, or the battery pack of claim 14.